A framework for quantification of human-structure interaction in vertical direction. (13th October 2018) - Ahmadi, Ehsan; Caprani, Colin; Živanović, Stana; Evans, Neil; Heidarpour, Amin
Abstract: In lightweight structures, there is increasing evidence of the existence of interaction between pedestrians and structures, now commonly termed pedestrian-structure interaction. The presence of a walker can alter the dynamic characteristics of the human-structure system compared with those inherent to the empty structure. Conversely, the response of the structure can influence human behaviour and hence alter the applied loading. In the past, most effort on determining the imparted footfall-induced vertical forces to the walking surface has been conducted using rigid, non-flexible surfaces such as treadmills. However, should the walking surface be vibrating, the characteristics of human walking could change to maximize comfort. Knowledge of pedestrian-structure interaction effects is currently limited, and it is often quoted as a reason for our inability to predict vibration response accurately. This work aims to quantify the magnitude of human-structure interaction through an experimental-numerical programme on a full-scale lively footbridge. An insole pressure measurement system was used to measure the human-imparted force on both rigid and lively surfaces. Test subjects, walking at different pacing frequencies, took part in the test programme to infer the existence of the two forms of human-structure interaction. Parametric statistical hypothesis testing provides evidence on the existence of human-structure interaction. In addition, a non-parametric test (Monte Carlo simulation) is employed to quantify the effects of numerical model error on the identified human-structure interaction forms. It is concluded that human-structure interaction is an important phenomenon that should be considered in the design and assessment of vibration-sensitive structures.